Analisa Faktor Kunjungan Wisatawan Mancanegara dan Penginapan Hotel Terhadap Penerimaan Sub Sektor PDRB pada Industri Pariwisata di Kabupaten Jember Tahun 2008-2018 - Helmi Agus Salim (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
Indonesia is one country with enormous natural resource potential that can be maximized in the tourism industry sector. Besides that, there is great hope that this tourism sector can increase PDRB in an area. According to the results of the analysis, this study shows the influence of the number of foreign tourist visits and hotel occupancy on the receipt of the tourism industry's PDRP sector in 2008-2018. The data used is time series data from the Central Bureau of Statistics and the Department of Tourism. This research uses quantitative research methods and uses partial addjustmen models using time series processes. In this study, the independent variables are foreign tourists (W1) and hotels (H2) while the dependent variable is PDRP (R). The results of the study using known multiple regression analysis and simultaneous regression test (F test) note that F -st5959.6 confidence below 1 percent indicates that foreign tourists and hotels have a significant effect on PDRP in Jember Regency. Partial regression test (t test) shows that there is a significant influence between the variables of foreign tourists and hotel occupancy on the PDRP of Jember Regency. The magnitude of the effect is that (R2) of 0.95. This means that the PDRP as the dependent variable is explained by the independent variables namely foreign tourists and hotel occupancy by 95% and the remaining 5% is explained by other variables outside the research.